2014
DOI: 10.1371/journal.pone.0086900
|View full text |Cite
|
Sign up to set email alerts
|

Increased Amygdala Response to Shame in Remitted Major Depressive Disorder

Abstract: Proneness to self-blaming moral emotions such as shame and guilt is increased in major depressive disorder (MDD), and may play an important role in vulnerability even after symptoms have subsided. Social psychologists have argued that shame-proneness is relevant for depression vulnerability and is distinct from guilt. Shame depends on the imagined critical perception of others, whereas guilt results from one’s own judgement. The neuroanatomy of shame in MDD is unknown. Using fMRI, we compared 21 participants w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 61 publications
3
33
0
Order By: Relevance
“…Specifically, amygdala activation to negative faces has been replicated in major depressive disorder (MDD) (1118) and is associated with the ruminative quality (19) and negative bias to emotional information in MDD (20) that represents exaggerated responses to negative emotional stimuli. Heightened amygdala activity to negative emotional stimuli (1115,1721) may also serve as a marker of persistent effects of past MDD, which was shown in some (2123) but not other studies (14,17,24,25) of individuals who recovered from depression versus controls.…”
Section: Salience/fear Networkmentioning
confidence: 99%
“…Specifically, amygdala activation to negative faces has been replicated in major depressive disorder (MDD) (1118) and is associated with the ruminative quality (19) and negative bias to emotional information in MDD (20) that represents exaggerated responses to negative emotional stimuli. Heightened amygdala activity to negative emotional stimuli (1115,1721) may also serve as a marker of persistent effects of past MDD, which was shown in some (2123) but not other studies (14,17,24,25) of individuals who recovered from depression versus controls.…”
Section: Salience/fear Networkmentioning
confidence: 99%
“…Interestingly, studies on shame and guilt [15] have also reported findings in amygdala and dorsal anterior cingulate cortex (dACC) that are hyper-responsive in PTSD [18]. For instance, Pulcu et al [19] detected increased amygdala response to shame in remitted major depressive disorder. For another example, Wagner et al [20] found that guilt in healthy subjects elicited stronger activations in dACC and amygdala than shame.…”
Section: Introductionmentioning
confidence: 99%
“…162 Our findings support cognitive models such as the constructive episodic simulation hypothesis, 165,166 as we show that the neural structures underpinning attentional biases also underpin prospective ones. Other research has found that pSTS activity is related to remembering and imagining socially threatening situations; 71,72 and is increased during such simulations in individuals with SAD. 167 Surprisingly, we did not find that amygdala volume directly correlates with individuals' STE, despite its wellestablished role in threat processing, including anticipation of social evaluation 168 and a proposed role in mediating temperamental shyness.…”
Section: Vbm Findings -Correlations With Social Threat Expectanciesmentioning
confidence: 90%
“…70 The pSTS and amygdala are also active during the simulation of social evaluative threat and embarrassment. 71,72 Here, we used VBM to identify correlations between SRE and/or STE and rGMV across the whole brain. We dissected and quantified the unique and overlapping rGMV correlates of SRE and STE using a combination of raw LODESTARS scores and LODESTARS scores that were orthogonalised (residualised) with respect to one another.…”
Section: Introductionmentioning
confidence: 99%